BENEFITS OF MINDFULNESS MEDITATION IN REDUCING BLOOD PRESSURE AND STRESS IN PATIENTS WITH ARTERIAL HYPERTENSION. (June 2018) - Ponte, P.; Castella, M.; Filella, D.; Feliu, A.; Matas, L.; Soler, J.; Ruiz, M.; Sole, M.J.; Ferrero, M.; Aguilera, M.; Roca-Cusachs, A.; Arroyo, J.A.
Abstract : Objective: To evaluate the benefits of mindfulness meditation in the control ambulatory blood pressure (BP) and the impact of the intervention on levels of anxiety, stress and depression Figure. No caption available. Design and method: Randomized controlled trial of a Mediterranean population with high-normal BP or grade I hypertension. 24 and 18 patients [n = 42; mean age 56.5 (7.7) years; similar proportions of men and women] were enrolled to an intervention and a control group, respectively. For 2 hours/week over 8 weeks, the intervention group received mindfulness training and the control group attended health education talks. The patients attended pre-intervention (baseline), week 4, week 8 and week 20 (follow-up) visits. Results: 61.9% of the patients had anxiety, 21.4% depression, 19.0% were smokers and 14.2% were diabetic (no significant differences between the 2 groups). At baseline, the intervention group had non-significant higher clinically measured BP values, whereas both groups had similar ambulatory BP monitoring (ABPM) values. At week 8, the intervention group had statistically significant lower ABPM scores than the control group [124/77 mmHg vs 126/80 mmHg (p < 0.05) and 108/65 mmHg vs 114/69 mmHg (p < 0.05) for 24-hour and night-time systolic BP (SBP), respectively] and also had lower clinically measured SBP values (130 mmHg vs 133 mmHg; p = 0.02). At week 20 (follow-up), means were lower in the intervention group (although not statistically significant). Improvements were observed in the intervention group in terms of being less judgemental, more accepting and less depressed. The results are shown in the table 1 and Figure 1. Conclusions: By week 8 the mindfulness group had lower clinically measured SBP, 24-hour SBP, at-rest SBP and diastolic BP values.